Lifestyle Intervention for the Prevention of Diabetes in Women With Previous Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis - Goveia, Pâmella; Cañon-Montañez, Wilson; Santos, Danilo de Paula; Lopes, Gabriela W.; Ma, Ronald C. W.; Duncan, Bruce B.; Ziegelman, Patricia K.; Schmidt, Maria Inês (Frontiers in Endocrinology, 2018)
Background: Type 2 diabetes is increasing among the young, and gestational diabetes (GDM) offers a unique opportunity for diabetes prevention. We systematically reviewed postpartum randomized trials to summarize the benefits of lifestyle interventions in the prevention of diabetes after GDM. Methods: We searched for all RCTs involving women with previous GDM that compared lifestyle interventions– diet, physical activity or breastfeeding– with usual care and without pharmacological treatment up to May 2018 following orientations of the PROSPERO statement. Results: Of 1,895 abstracts identified, we selected 15 studies investigating incident diabetes or changes in glycemia. Most interventions focused on changes in diet and physical activity, only one also on incentive to breastfeeding. Meta-analysis of 8 studies investigating incident diabetes revealed a homogeneous (I2=0.2%), borderline significant reduction of 25% (RR=0.75; 95%CI: 0.57-1.00) in incidence. When stratified by time of randomization, only studies initiating <6 months post-partum were effective (RR=0.66; 95%CI:0.47-0.92; p for subgroup comparison=0.17). Overall, no benefit was found regarding measures of glycemia. Moderate reductions in weight (MD=-1.07kg; -1.43kg - -0.72kg); BMI (MD=-0.94kg/m2; -1.79kg/m2 - -0.09kg/m2; and waist circumference (MD=-0.98cm; -1.75cm - -0.21 cm) occurred. Effects were larger with longer follow-up. Conclusions: Lifestyle interventions after a pregnancy complicated by GDM appear beneficial. Their effects on the incidence of diabetes and on anthropometrics, though smaller than those of the classic studies of diabetes prevention through lifestyle changes, are of clinically relevant size. Further tailoring of the delivery of lifestyle interventions soon after a pregnancy complicated by GDM is needed to improve their effectiveness.